Analysis of Wage Administration and Article 21 Income Tax for Employees with Income below the Non-Taxable Income Threshold - Meliana Anggraini; Deviana Sari; Chairian Tomy (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the implementation of wage administration and the fulfillment of Income Tax (PPh) Article 21 obligations for production employees whose income is below the Non-Taxable Income threshold. The research method used is descriptive qualitative, with data collection techniques including participatory observation and documentation study. Data analysis was conducted using a simulation of average income index, rather than actual employee income data, in order to maintain data confidentiality while still providing a representative overview of wage conditions. The results show that the company’s wage system applies an index-based method that integrates physical attendance (fingerprint) with fluctuating wage components such as meal allowances, transportation, and incentives. Based on the simulation using the annual net income calculation formula, the average income of production employees is below the Non-Taxable Income threshold for the TK/0 category (Rp54,000,000), resulting in a “Nil” tax status. Nevertheless, the company demonstrates a high level of administrative compliance through transparent payslip management and systematic tax reporting. This indicates that orderly administration is crucial for maintaining the accuracy of labor cost data and ensuring the company’s fiscal compliance readiness in the future.